Topological Aspects of Boron Nanotubes. (4th July 2018) - Liu, Jia-Bao; Shaker, Hani; Nadeem, Imran; Hussain, Muhammad
Abstract : The degree-based topological indices are used to correlate the physical and chemical properties of a molecule with its chemical structure. Boron nanotubular structures are high-interest materials due to the presence of multicenter bonds and have novel electronic properties. These materials have some important issues in nanodevice applications like mechanical and thermal stability. Therefore, they require theoretical studies on the other properties. In this paper, we present certain degree-based topological indices such as A B C, the fourth A B C, G A, and the fifth G A indices for boron triangular and boron- α nanotubes.